The Role of Associative Cortices and Hippocampus during Movement Perturbations - Kerr, Matthew S. D.; Sacré, Pierre; Kahn, Kevin; Park, Hyun-Joo; Johnson, Mathew; Lee, James; Thompson, Susan; Bulacio, Juan; Jones, Jaes; González-Martínez, Jorge; Liégeois-Chauvel, Catherine; Sarma, Sridevi V.; et al. (Frontiers in Neural Circuits, 2017)
Although motor control has been extensively studied, most research involving neural recordings has focused on primary motor cortex, pre-motor cortex, supplementary motor area, and cerebellum. These regions are involved during normal movements, however, associative cortices and hippocampus are also likely involved during perturbed movements as one must detect the unexpected disturbance, inhibit the previous motor plan, and create a new plan to compensate. Minimal data is available on these brain regions during such “robust” movements. Here, epileptic patients implanted with intracerebral electrodes performed reaching movements while experiencing occasional unexpected force perturbations allowing study of the fronto-parietal, limbic and hippocampal network at unprecedented high spatial and temporal scales. Areas including orbitofrontal cortex (OFC) and hippocampus showed increased activation during perturbed trials. These results, coupled with a visual novelty control task, suggest the hippocampal MTL-P300 novelty response is modality independent, and that the OFC is involved in modifying motor plans during robust movement.